Investigation on reversible pump turbine flow structures and associated pressure field characteristics under different guide vane openings - Binama, Maxime; Su, WenTao; Cai, WeiHua; Li, FengChen; Wei, XianZhu; Muhirwa, Alex; Gong, RuZhi; Wekesa, David W (Science China Press, 2019)
The use of reversible pump turbines (RPT) within pumped storage power plants goes with prolonged periods of off-design operating conditions, which leads to the onset of operating mode-dependent instabilities. In order to if not eliminate then decrease the gravity of RPT flow instabilities and associated damages, a deep understanding of its onset and development mechanism is needed.In line with this,the present study seeks to numerically investigate the on set and development mechanism of RPTun steady flow structures as well as the evolutional characteristics of associated pressure pulsations throughout the RPT complete flow passage, under off-design conditions for three GVOs namely 17, 21, and 25mm. The study results showed that low torque operating conditions and associated vane less space back flow structures were the trigger offlow unsteadiness onset within the RPT vane less space,the instabilities which grew to cause the s shape characteristics appearance.Moreover,the runner flow unsteadiness was found to decrease with the GVO increase. On the other hand, the GVO increase worsened the pressure pulsation levels within RPT flow zones,where pressure pulsations within the vaneless space and flow zones in its vicinities were found to be the most sensitive to GVO changes.
Keywords: Reversible pump-turbine; Flow unsteadiness; Pressure pulsation; Guide vane opening; Numerical simulation